An Analysis Of Electric Energy Monitoring And Protection Based On Smart Interface Systems - Mardi Sijabat; Muhammad Erpandi Dalimunthe; Rahmaniar, Rahmaniar (Jurnal Scientia, 2024)
This research aims to analyze an electrical energy monitoring and protection system based on a smart interface system. In the current digital era, the need for systems that are more efficient, reliable and easily accessible is very high, especially in terms of electrical energy management and protection. Smart interface systems offer solutions to improve monitoring and protection capabilities through the use of advanced technology and automation. Research methods include the development and implementation of a smart interface system consisting of advanced sensors, wireless communication modules, and web-based monitoring software. This system is designed to detect various electrical parameters such as voltage, current and frequency in real-time, and provide automatic protection responses when anomalies or disturbances occur. The research results show that the smart interface system is able to increase the reliability and efficiency of monitoring and protection of electrical energy. This system successfully detects and responds to disturbances quickly, reduces the risk of equipment damage, and minimizes operational downtime. In addition, the intuitive user interface makes it easier for operators to monitor and manage electrical energy systems. The implementation of a smart interface system for monitoring and protecting electrical energy provides many benefits, including increased operational efficiency, system reliability and ease of management. This research contributes to the development of more advanced and reliable monitoring and protection technology, as well as providing recommendations for wider application in various industries that depend on complex electrical energy systems.